School principal leadership in transmigration areas to improve the quality of education - Pratiwi Pratiwi; Rambat Nur Sasongko; Connie Connie (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study explores the leadership practices of school principals in transmigration areas to improve education quality, identifying key supporting and inhibiting factors, along with potential solutions. The research employed a descriptive qualitative approach with data collection techniques consisting of in-depth interviews, direct observation, and document analysis involving principals, teachers, supervisors, and school committees. Findings indicate that the principal applied an Integrated Adaptive Leadership (IAL) model, which combines charismatic, situational, democratic, transformational, servant, and instructional approaches. This leadership integration proved effective in strengthening teacher competence, participatory school management, and a positive school culture, thereby contributing to improvements in the input, process, and output dimensions of education quality. Supporting factors for leadership success include teacher loyalty, a conducive school climate, and active community engagement, while inhibiting factors consist of limited facilities and infrastructure, low technological competence, insufficient government support, and the socio-economic conditions of the community. Solutions identified encompass capacity strengthening for principals and teachers, greater utilization of information technology, enhancement of community participation, and active advocacy to local government. The novelty of this study lies in its direct exploration of principal leadership in transmigration areas, explicitly linked to educational quality indicators in the Education Report. Practically, the research provides important implications for principals, education authorities, and communities in formulating context-sensitive strategies to improve education quality. Theoretically, its contribution extends the study of educational leadership into marginalized and under-resourced settings.